Pathways and Inborn Errors of Bile Acid Synthesis - Obuz, Ufuk Bozkurt; Lay, Incilay (Acta Medica, 2019)
Bile acids are synthesized from cholesterol through 17 different enzymes located in different intracellular compartments of hepatocytes. Defects have been identified in the genes encoding the enzymes involved in the bile acid synthesis pathways and nine different diseases have been identified so far. In this review, four different biosynthetic pathway of bile acids together with disorders of bile acid synthesis is described. In inborn errors of bile acid synthesis clinical findings can range from liver failure to cirrhosis in infancy or progressive neuropathy in adolescence / adulthood. Laboratory analysis of urine profiling of bile acids is important in early diagnosis and early treatment.